Simultaneously Sizing and Quantitating Zeptomole‐Level DNA at High Throughput in Free Solution. Issue 43 (15th September 2014) - Zhu, Zaifang; Chen, Huang; Chen, Apeng; Lu, Joann J.; Liu, Shaorong; Zhao, Meiping
Abstract: Determining the sizes and measuring the quantities of DNA molecules are fundamental tasks in molecular biology. DNA sizes are usually evaluated by gel electrophoresis, but this method cannot simultaneously size and quantitate a DNA at low zeptomole (zmol) levels of concentration. We have recently developed a new technique, called bare‐narrow‐capillary/hydrodynamic‐chromatography or BaNC‐HDC, for resolving DNA based on their sizes without using any sieving matrices. In this report, we utilize BaNC‐HDC for measuring the sizes and quantities of DNA fragments at zmol to several‐molecule levels of concentration. DNA ranging from a few base pairs to dozens of kilo base pairs are accurately sized and quantitated at a throughput of 15 samples per hour, and each sample contains dozens of DNA strands of different lengths. BaNC‐HDC can be a cost‐effective means and an excellent tool for high‐throughput DNA sizing and quantitation at extremely low quantity level. Abstract : DNA and chips : A splitting‐based microchip injector was incorporated with BaNC‐HDC for high‐throughput DNA analysis without using any sieving matrix. The integrated system was capable of simultaneously sizing and quantitating at the single‐molecule level (see figure).